Masalah dan Dinamika Industri Kecil Pasca Krisis Ekonomi - Y. Sri Susilo; A. Edi Sutarta (Universitas Islam Indonesia, 2004)
This research is aimed at measurement and analysis of problem and also dynamic of small scale industry in post economic crisis environment, especially in the year of 2002. The industry studied includes small scale and household-handicraft industry. The research meth¬odology used consists of: (1) literature study, (2) field survey, and (3) focus group discussion (FGD).The conclusion of this research shows that the problem and dynamic faced by small scale and household handicraft industries have similarities and differences among different kind or group of industries. The major similarity is the problem of increasing input prices that force them to raise their products price. Another similarity is the decreasing quantity of output and employment.The differences depend on the kind and feature of each small scale and household handicraft industry. Some say that their major problem is the raw material supply, and some say that their major problem is their competitiveness in market. Nevertheless, some small scale and household handicraft industries say that their major problem is the marketing of their product and also the availability of skilled labor.Keywords: small scale industry, dynamic, production, employment.